Learning CAD Ukrainian engineers - Самотокін, Б.Б.; Зайончковський, Г.Й. (Proceedings of National Aviation University, 2009)
All universities that implemented the project are part of this program. This is a vivid example of the effectiveness of cooperation between Ukrainian universities with the European Commission to improve the preparation of graduates of Ukrainian universities.